Develop an Al-alloy for high pressure-high temperature applications by enhancing thermo-mechanical properties - Joy Mathavan, J.; Kunaraj, A.; Sakthivelnathan, N. (Springer link, 2021)
The aim of this research work is to develop an aluminium alloy which can be used in conditions like high temperature and high pressure. High pressure die castings, specially engine components of automobiles and heavy vehicles are the important components which need to survive in such challenging working environment. Silicon, Nickel and Chro- mium found to be suitable filler materials to be used in high pressure and high temperature conditions based on literature reviews. Based on the individual physical, chemical and thermo-mechanical properties of Si, Ni and Cr, these elements were selected as alloying elements and alloys Al- Si, Al-Si-Cr and Al-Si-Ni were prepared. The prepared samples were tested for various thermo-mechanical properties and the results were an- alyzed. Tensile strength values are obtained from hardness values based on Mayer’s hardness. Thermal conductivity values were obtained from electrical conductivity values based on Wiedemann–Franz law. Void content is calculated from practical and theoretical density values. At the end of the research, the new aluminium alloys proposed in this work found to be better replacements for aluminium metal which is currently in use for many high pressure high temperature applications.
Keywords: Thermo-mechanical property; Al alloy; Engine components